Pengembangan Keterampilan Komputer Dasar untuk Siswa Sekolah Dasar di Daerah Pedesaan: Studi Kasus Desa Saringembat - Taufikurrahman Taufikurrahman; Muhammad Rafi Arganta; Sania Fitria Rahmah; Safiira Alby An Nabiilah; Ni Made Priyamka Armadani Pradnya Santo (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The development of basic computer skills in primary school students in rural areas remains a challenge. This community service activity aims to develop basic computer skills for primary school students in Saringembat Village, a rural area with limited access to information technology. The program is designed to improve students' digital literacy through intensive training that includes hardware introduction, basic software operation, and technology application in daily learning activities. The implementation approach involves active participation from teachers, and parents. Training methods include hands-on practice sessions, group discussions and skills evaluation through quizzes. The results of the activities show significant improvements in students' understanding and ability to use computers to support learning. This program has a positive impact on improving digital literacy in rural areas and is expected to be replicated in other areas with similar conditions.